The usage of renewable energy sources and its effects on GHG emission intensity of electricity generation in Turkey - Sahin, Habip; Esen, Hikmet (Pergamon-Elsevier Science Ltd, 2022)
The aim of this study is to analyze the use of renewable energy resources in electricity generation and its impacts on greenhouse gas emissions mitigation in terms of emission intensity in Turkey. Thus, annual development of Turkey's electricity generation by renewable energy resources and its share in general total were examined. Annually, total greenhouse gas emissions from electricity production are determined and divided by total electricity production so that the emission intensity from electricity production is found in gCO(2)e/kWh. The effect of each source used in electricity generation on the emission intensity is demonstrated. Although there are volatilities in some years, it is revealed that the emission intensity, which was 563 gCO(2)e/kWh in 2008, decreased to 437 gCO(2)e/kWh in 2020 with an annual average decrease of 2.1%. These emission data belonging to Turkey are compared with the values of the European Union since it is a candidate country. As a result, it has been suggested that Turkey, which has a large renewable energy potential, should use this potential more effectively in order to further reduce its emissions from electricity generation. (C) 2022 Published by Elsevier Ltd.
Keywords: Renewable energy; Electricity generation; Greenhouse gas emission; Emission intensity